A stepped approach for the management of symptomatic internal derangement of the temporomandibular joint - Candan Efeoglu; Aylin Sipahi Calis; Huseyin Koca; Esra Yuksel (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Internal derangement is the clinical and pathological condition of disc displacement of the temporomandibular joint. Management of these cases involve conservative and surgical treatment options. Minimally invasive surgical procedures namely arthrocentesis and arthroscopy are promising techniques in the management of internal derangement. However patient selection algorithms, indications for minimally invasive procedures and details of the techniques should be further studied for safe and cost effective management of these cases. This manuscript aims to retrospectively analyze the significance of a stepped surgical treatment approach (arthrocentesis under local anaesthesia as the first line of treatment, followed by arthroscopic lysis and lavage under general anaesthesia in unresolving cases) of internal derangement with or without osteoarthritis. Methods This is a retrospective cohort study. Case notes of 1414 patients that were managed with a standard protocol were reviewed. Appropriate inclusion and exclusion criteria were set. Thirty-three patients were eligible for inclusion. Parameters recorded were pain-free inter-incisal opening, spontaneous pain, pain on function, difficulty on chewing, and perceived disability on jaw movements. Pre-operative and post-operative (at the end of the follow up period) pain free maximum interincisal opening values were compared with paired t test and the subjective parameters were evaluated with Chisquare analysis. Treatment outcome and success rate according to American Association of Oral and Maxillofacial Surgeons were descriptively shown. Results Interincisal opening values increased, and the number of patients with severe or medium rated subjective parameters were reduced at discharge. These improvements were found to be statistically significant. Clinical (Wilkes) staging of internal derangement pre-operatively and at discharge remained either unchanged or was lower. Treatment outcome and success according to American Association of Oral and Maxillofacial Surgeons criteria was 94%. Conclusion The stepped approach for the management of symptomatic internal derangement with or without osteoarthritis is a successful treatment strategy with favourable therapeutic outcomes.